Validity and reliability of three-dimensional scanning compared with conventional anthropometry for children and adolescents-response to the rebuttal by Sabour - Glock, Fabian; Scholz, Markus; Kühnapfel, Andreas; Kiess, Wieland (Pediatric research, 2017)
Pediatric Research accepted article preview online, 29 March 2017. doi:10.1038/pr.2017.76.